The Effect of Single-Dose Antenatal Dexamethasone in Reducing Respiratory Complications in Late Preterm - Adisak Waiketkarn; Charintip Somprasit; Chamnan Tanprasertkul (The Royal Thai College of Obstetricians and Gynaecologists, 2020)
Objectives: To determine the effect of a single dose of dexamethasone in reducing respiratory complications in late preterm newborns.Materials and Methods: This was a prospective cohort study. Pregnant women who were at risk of preterm births at 340/7 - 366/7 weeks of gestation were prospectively observed. The first group was given single dose of antenatal dexamethasone, while the second group received only the standard treatment without dexamethasone as the control group. The main outcomes are rate of respiratory complications in newborns.Results: A total of 205 pregnant women who were enrolled with complete data for analysis. Sixty-eight and 137 were in the single dose and control groups, respectively. The rates of respiratory complications in all gestational ages between the two groups were not significantly different (22.1% and 32.8%, respectively: p = 0.11). Multivariate logistic regression model was utilized to adjust confounders for independent factors of respiratory complications in late preterm newborns. A single dose of dexamethasone and gestational age at 360/7-6/7 weeks became significant factors in order to decrease respiratory complication rate and received an adjusted odds ratio of 0.45 and 0.29 at p = 0.03 and p = 0.001, respectively.Conclusion: Administration of a single dose of dexamethasone is a factor in reducing rate of respiratory complications in late preterm newborns without any seriously adverse effects.